Design of Software and Hardware Complex of Temperature Field Diagnostics using the Theory of Distributed Parameter Systems - Novozhilov, Igor M.; Sidorenko, Andrei A.; Tukeyev, Dmitrii L.; Podkina, Maria E.; Pervukhin, Dmitrii A.; Trushnikov, Vyacheslav E. (2023 V International Conference on Control in Technical Systems (CTS), 2023)
This research designs a hardware-software platform for diagnosing the temperature field of a moving oil stream. The theory of distributed parameter systems and similarity theory are chosen as the subject of the study. Arduino technology and software development environment in Delphi language Embarcadero RAD Studio XE7 are used as hardware.